Mental health help-seeking knowledge, attitudes and behaviour among male elite rugby players: the role of masculine health-related values - Simon M Rice; John L Oliffe; Yasutaka Ojio; Rei Amemiya (BMJ Open Sport & Exercise Medicine, 2025)
Objectives Masculine norms of toughness and self-reliance can discourage help-seeking among elite athletes who are men. Effective ways to leverage masculine norms for help-seeking is a relatively unexplored area in athlete mental health. The study aimed to investigate how masculine health-related values measured by the Intentions Masculine Values Scale (IMVS) affect help-seeking behaviours among male elite rugby players.Methods A cross-sectional survey was conducted among 220 Japanese male elite rugby players in the Japan Rugby League One (response rate: 40.6%). Participants completed an online survey assessing help-seeking knowledge, attitudes and behaviours, along with masculine health-related values using the IMVS. Psychological safety within sports settings was evaluated using the Sport Psychological Safety Inventory (SPSI). Multiple regression analyses examined relationships between help-seeking behaviours and IMVS/SPSI.Results The Open and Selfless IMVS value was significantly associated with help-seeking knowledge (β=0.059, p=0.009) and attitudes (β=0.064, p=0.006), increasing recognition of the need for help and willingness to seek it. However, no significant association with actual help-seeking behaviour was found (β=−0.006, p=0.774). The Healthy and Autonomous IMVS value was associated with lower help-seeking behaviour (β=0.060, p=0.010), indicating higher autonomy may inhibit seeking professional support. The SPSI was not significantly related to help-seeking measures.Conclusion Findings highlight critical gaps between intention and actual help-seeking behaviour among male elite athletes. Further research is needed to explore additional cultural and organisational factors that may better explain help-seeking behaviour and inform effective intervention strategies.